No Business Taxation Without Model Representation : Adding Corporate Income and Cash Flow Taxes to GIMF - Carton, Benjamin (IMF Working Papers; Working Paper, 2017)
The Global Integrated Monetary and Fiscal model (GIMF) is a multi-region, forward-looking, DSGE model developed at the International Monetary Fund for policy analysis and international economic research. This paper documents the incorporation of corporate income, cash-flow and destination based cash-flow taxes into the model. The analysis presented considers the transmission mechanism of these taxes and details how financial frictions interact with each of the taxes.